2015
DOI: 10.1111/jorc.12122
|View full text |Cite
|
Sign up to set email alerts
|

IgA NEPHROPATHY IN PATIENTS RECEIVING A RENAL TRANSPLANT

Abstract: The rate of post-transplant IgA diagnosis in our case series was 11%, and IgAN was diagnosed late in the course of transplantation. In most cases, IgAN manifested as haematuria and non-nephrotic proteinuria, without renal graft dysfunction, and this picture might explain late indication of graft biopsies. The 10-year patient survival rates were excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…[ 25 ] Data from a large tertiary care military hospital in North India have revealed an estimated graft survival at 5 years of 80.5%. [ 26 ] The available studies comparing the graft survival of posttransplant IgAN patients with overall survival show variable outcomes[ 10 11 12 13 14 18 27 28 29 30 31 32 33 34 35 36 ] as shown in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 25 ] Data from a large tertiary care military hospital in North India have revealed an estimated graft survival at 5 years of 80.5%. [ 26 ] The available studies comparing the graft survival of posttransplant IgAN patients with overall survival show variable outcomes[ 10 11 12 13 14 18 27 28 29 30 31 32 33 34 35 36 ] as shown in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] For posttransplant IgAN, most studies showed that patients with clinical recurrence of IgAN have a lower long-term graft survival than patients without recurrence. [ 7 11 13 16 18 31 32 33 34 35 36 ] Local variations in patient demographics and medical practice can contribute to differences in renal outcomes in patients with IgAN in native kidney disease. [ 37 ] These local variations might be important in the posttransplant IgAN as well.…”
Section: Discussionmentioning
confidence: 99%